RESULTS OF POSTERIOR ROTATIONAL OSTEOTOMY OF THE FEMUR IN CHILDREN - Ashirov Mavlon Umirzakovich; Ishkabulov Rustam Dzhankhurazovich; Muradova Aziza Utkir kizi; Ashirov Farrukhbek Azamat Ugli (European Science Publishing, 2025)
Rotational femoral osteotomies are rarely used in the treatment of hip pathology. Rotational osteotomies allow you to change the spatial position of the head and neck of the femur in three planes; with their help, it is possible to restore normal relationships in the hip joint and congruence of the articular surfaces, and remove the deformed or destroyed sector of the femoral head from stress.